Sex pheromone of the processionary moths and biosystematic considerations within the genus Thaumetopoea (Thaumetopoeidae Thaumetopoeinae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Identification of sex pheromone within 5 species belonging to the Thaumetopoeidae family are reported in this paper. Chemistry of the pheromone components corroborated the split between two types of processionary moths on the insect biology: ie the winter and summer processionary moths. Pheromone chemistry tend also to support the fact that T. pityocampa and T. wilkinsoni should be considered as ecotypes. The same conclusion is proposed for T. pinivora and T. bonjeani.
Keywords: Lepidoptera; Thaumetopoeidae; chemotaxonomy; chemical identification; ecotypes